The relationship between the composite dietary antioxidant index and rheumatoid arthritis risk in American adults: the mediating role of BMI - Gao, Tao; Chen, Zhi-Yu; Li, Tao; Tang, Jian-Dong; Lin, Xu; Hu, Hai-Gang; Wan, Sheng-Yu; Wu, Chao (Frontiers in Immunology, 2025)
BackgroundThe Clinical Dietary Antioxidant Index (CDAI) is a dietary antioxidant assessment index. Although CDAI has been shown to play a role in various chronic diseases, its association with rheumatoid arthritis (RA) remains underexplored. The aim of this study was to investigate the relationship between the CDAI and RA in U.S. adults, and to examine the mediating role of body mass index (BMI) in the relationship between CDAI and RA incidence.MethodsThis cross-sectional study utilized data from the 2015–2023 National Health and Nutrition Examination Survey (NHANES). Weighted multivariate logistic regression models, restricted cubic spline (RCS) functions, and subgroup analyses were employed to examine the association between CDAI levels and RA in American adults. Mediation analysis was conducted to explore the mediating role of BMI in the relationship between CDAI and RA incidence.ResultsA total of 13,288 participants were included, of whom 787 were diagnosed with RA, with a prevalence rate of 5.9%. Weighted multivariate logistic regression analyses across all four models showed a negative correlation between CDAI levels in the highest quartile and RA incidence. Restricted cubic spline curves revealed a non-linear negative association between CDAI, vitamin E, carotenoids, selenium, and RA incidence. As levels of CDAI, vitamin E, carotenoids, and selenium increased, the risk of RA decreased. Subgroup analyses and forest plots indicated significant associations between CDAI levels and RA across subgroups, including females, individuals aged over 60 years, Other Race - Including Multi-Racial groups, smokers, non-drinkers, individuals with heavy physical activity, hypertension, and BMI >25 (P < 0.05). Mediation analysis showed that BMI partially mediated the relationship between CDAI and RA, accounting for 10.88% of the effect.ConclusionsCDAI levels were negatively associated with RA incidence, particularly the components of CDAI such as vitamin E, carotenoids, and selenium. BMI mediated the relationship between CDAI and RA.